Improving the Ability to Understand the Quran Reading through the Application of the Mind Map Method during the Covid 19 Pandemic in Al-Qur'an Education Institutions Qurrota A'yun at Kutaraja Village, Maleber District, Kuningan Regency - Saepudin, Saepudin; Kartika, Ika; Suhada, Ahmad; Ahyudin, Didin; Agustianty, Efit Fitria; Arjadisastra, Nasihin; Hidayat, Rohman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Qur'an house "Qurotu A'yun" Kutaraja Village, Maleber District, Kuningan Regency, West Java is a religious institution whose learning focus is memorizing the Qur'an and is one of the institutions affected by the Covid 19 pandemic that occurred. The institution takes a learning policy outside the network by implementing health protocols. However, with the learning outside the network, there are still obstacles, including the ineffectiveness of the methods used in learning the memorization of the Qur'an by means outside the network. The method used in community service activities is to provide guidance to teachers and guardians of students in the use of the mind map method of understanding learning. The media used in coaching teachers is with zoom meetings, while the guidance that teachers do for students' guardians is carried out outside the network using health protocols. After coaching on the application of the mind map method, student learning outcomes increased from before and after applying the mind map method by 35.7 percent, so that in an effort to improve student understanding of the ability to read the Qur'an, it is necessary to apply the mind map method in learning to read the Qur'an.